Systematic Journal Review: The Effect of Age and Obesity on Chronic Rhinitis and Allergic Rhinitis - Nabila Azzahra Permata Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Chronic rhinitis and allergic rhinitis are common inflammatory upper airway diseases with substantial clinical impact. Age and obesity are considered potential determinants influencing disease occurrence and presentation. This study aimed to systematically evaluate the effects of age and obesity on chronic rhinitis and allergic rhinitis. A Systematic Journal Review was conducted following PRISMA guidelines. Literature searches were performed in PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar from 2020 to 2025. Eligible studies were qualitatively analyzed using narrative synthesis. Ten primary studies were included in the final analysis. Older age was consistently associated with a higher prevalence of non-allergic chronic rhinitis, while allergic rhinitis predominated in children and young adults. Obesity was significantly associated with chronic rhinitis in adults. However, findings regarding obesity and allergic rhinitis in children and adolescents were inconsistent. The interaction between age and obesity influenced clinical phenotype and disease severity. Age and obesity significantly affect rhinitis occurrence with distinct patterns across age groups.